Chlorophyll and Carotenoid Level Comparisons of Pigeon Orchid (Dendrobium crumenatum) in Water and Light Stress Treatment - Febri Yuda Kurniawan; Dea Evani Amelia (Indonesian Journal of Science and Education (IJOSE), 2021)
Environtmental conditions in which plants grow are always changing which when exceeding the tolerance limit will result in stress. Water and light stress affect the pigment content of photosynthesis such as chlorophyll and carotenoids. Dendrobium crumenatum is one of orchid species that is judged to be resistant to various types of environtmental conditions, so it can grow well in any environtment. This research aims to determine the comparison of chlorophyll and carotenoid levels of D. crumenatum from Bantul lowland population, Special Region of Yogyakarta which is given water and light stress treatment. The methods used are extraction with alcohol solvent (96%) and absorbtion level measurements with spectrophotometry at wavelengths 470, 645, and 663 nm. The highest chlorophyll a level contained in the leaves of D. crumenatum which is given water stress treatment, highest chlorophyll b level in control plant, highest total chlorophyll in the leaves which is given water stress treatment, and highest carotenoid level found in the leaves which is given light stress treatment.